Egg cases of the graytail skate Bathyraja griseocauda and the cuphead skate Bathyraja scaphiops from the south-west Atlantic Ocean - Mabragaña, Ezequiel (2017)
Egg cases of Bathyraja griseocauda were larger (140?142mm in length) than those of Bathyraja scaphiops (88?90mm in length) and their surface was relatively smooth, without denticles, prickles or any ornamentation. Egg cases of B. scaphiops had a relative coarse surface, covered with pricklesof similar size. An identification key for the all described egg cases from Bathyraja occurring in the south-west Atlantic Ocean is provided.